Struktur Komunitas, Cadangan Karbon, dan Estimasi Nilai Ekonomi Mangrove di Muara Sungai Musi - Harum Farahisah; Fredinan Yulianda; Hefni effendi (Institut Pertanian Bogor, 2021)
Mangrove ecosystem services, aside for the fisheries sector, also have ecosystem services in mitigating climate change as carbon sinks and storage. Musi river estuary located in Banyuasin Regency, South Sumatra has the potential of mangrove forests as carbon reserves. The purpose of the study is to analyze the community structure, potential carbon stocks, and economic value of mangroves in the Musi River Estuary. Data were collected at five stations using the 100 m quadratic transect method vertically to the coastline. Data analysis was conducted based on the allometric equation for biomass information, carbon storage, and the economic value of carbon stores. Mangrove ecosystems in the Musi River estuary are Sonneratia alba, Nypa fruticans, Sonneratia casiolaris, and Rhizopora apiculata. Mangrove species that have important roles in the sustainability of ecosystems are Nypa fruticans and Sonneratia alba each with IVI of 145.6 and 101.28, respectively. Carbon storage of mangrove in the Musi river estuary is 107.34 tonC / ha and carbon dioxide absorption is 393.59 tCO2 / ha with a mangrove area of ± 5276 ha. The total estimated economic value of carbon generated from mangrove are Rp174.441.016.895 (free market) and Rp455.872.524.151 (CDM). Keywords: carbon, mangrove, Musi river estuary